The role of Wnt signaling in the healing myocardium: a focus on cell specificity - Meyer, Sören; Leuschner, Florian (Basic research in cardiology, 2018)
Various cell types are involved in the healing process after myocardial infarction (MI). Besides cardiac resident cells (such as cardiomyocytes, fibroblasts and endothelial cells) already present at the lesion site, a massive influx of leukocytes (mainly monocytes and neutrophils) is observed within hours after the ischemic event. So far, little is known about modes of interaction of these cells. Wnt signaling is an evolutionary conserved signaling cassette known to play an important role in cell-cell communication. While the overall reactivation of Wnt signaling upon ischemic injury is well described, the precise expression pattern of Wnt proteins, however, is far from understood. We here describe known Wnt components that partake in MI healing and differentiate cell-specific aspects. The secretion of Wnt proteins and their antagonists in the context of cardiac inflammation after MI appear to be tightly regulated in a spatial-temporal manner. Overall, we aim to stress the importance of elucidating not only Wnt component-specific aspects, but also their sometimes contradicting effects in different target cells. A better understanding of Wnt signaling in MI healing may eventually lead to the development of successful therapeutic approaches in an often considered "un-druggable" pathway.
Gesehen am 09.04.2020